Role of RING-Type E3 Ubiquitin Ligases in Inflammatory Signalling and Inflammatory Bowel Disease - Liguo Zhu; Ying Li; Longyuan Zhou; Guang Yang; Ying Wang; Jing Han; Li Li; Shenghong Zhang (Mediators of Inflammation)
Ubiquitination is a three-step enzymatic cascade for posttranslational protein modification. It includes the ubiquitin-activating enzyme (E1), ubiquitin-conjugating enzyme (E2), and ubiquitin ligase (E3). RING-type E3 ubiquitin ligases catalyse the posttranslational proteolytic and nonproteolytic functions in various physiological and pathological processes, such as inflammation-associated signal transduction. Resulting from the diversity of substrates and functional mechanisms, RING-type ligases regulate microbe recognition and inflammation by being involved in multiple inflammatory signalling pathways. These processes also occur in autoimmune diseases, especially inflammatory bowel disease (IBD). To understand the importance of RING-type ligases in inflammation, we have discussed their functional mechanisms in multiple inflammation-associated pathways and correlation between RING-type ligases and IBD. Owing to the limited data on the biology of RING-type ligases, there is an urgent need to analyse their potential as biomarkers and therapeutic targets in IBD in the future.